Adenosine deaminase and xanthine oxidase activities in bladder washing fluid from patients with bladder cancer - Güleç, M; Akin, H; Yüce, H; Ergin, E; Elyas, H; Yalçin, O; Akyol, Ö (Pergamon-Elsevier Science Ltd, 2003)
Activities of adenosine deaminase (AD), and xanthine oxidase (XO) enzymes were measured in bladder washing fluid (BWF) from 37 patients with bladder cancer. The patients were divided into several groups according to their sex; pattern, number, and depth of the tumors; and tumor grade. There was a statistically significant difference in XO activities between the patients having no tumor and papillary tumor (p < 0.002). The differences in XO values between the patients having no tumor and single tumor; and with no tumor and multiple tumors were statistically significant (p < 0.012, p < 0.016 respectively). XO activities were increased in patients with both papillary and multiple tumors compared to tumor-free group. Regarding to the depth of tumors, only the differences in XO values between the patients having no tumor and superficial tumor was statistically significant (p < 0.037). XO values of patients in grade 1 were higher than the patients having no tumor (p < 0.010). AD activities in patients with multiple and invasive tumor were increased compared to patients with single and superficial tumor. AD values in grade 3 were lower than grade 2. However, we did not find any statistically significant differences in AD activities in all groups. As a conclusion, increased XO activity in BWF might be a potentially important finding as an additional diagnostic biochemical tool for bladder cancer. But we could not say this for AD activity. Further investigations in a larger cohort of patients with bladder cancer are needed to enlighten the possible diagnostic role of XO and AD in BWF. (C) 2003 The Canadian Society of Clinical Chemists. All rights reserved.
Keywords: Superoxide-Dismutase; Catalase Activities; Human Tissues; Lung-Cancer; Enzymes; Carcinoma; Isozymes